2014
DOI: 10.1016/j.appet.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restriction on children’s intake differ by child temperament, food reinforcement, and parent’s chronic use of restriction

Abstract: Parents’ use of restrictive feeding practices is counterproductive, increasing children’s intake of restricted foods and risk for excessive weight gain. The aims of this research were to replicate Fisher and Birch’s (1999b) original findings that short-term restriction increases preschool children’s (3–5 y) selection, intake, and behavioral response to restricted foods, and to identify characteristics of children who were more susceptible to the negative effects of restriction. The experiment used a within-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
5
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 31 publications
5
90
5
2
Order By: Relevance
“…This dietary practice requires further study, particularly the context in which sweets are provided to children—sweets given as reward, for instance, can increase a child's risk of overweight due to poor self-regulation of appetite, problematic eating attitudes, and an increased preference for and consumption of sweet food. 54-56 …”
Section: Discussionmentioning
confidence: 99%
“…This dietary practice requires further study, particularly the context in which sweets are provided to children—sweets given as reward, for instance, can increase a child's risk of overweight due to poor self-regulation of appetite, problematic eating attitudes, and an increased preference for and consumption of sweet food. 54-56 …”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggest harm, because restrictions impair a child's self-regulation (Birch, Fisher and Davison 2003;Rollins et al 2014). In EAH studies, for example, children (ages 3-6, normal weight) had free or restricted access to equally liked snacks.…”
Section: Parenting Practices: Restricting Children's Consumption Of Umentioning
confidence: 99%
“…And the effects on children are not only immediate: a high level of restriction imposed at age five predicts girls' EAH at ages seven and nine (Birch et al 2003). Children of certain temperaments, especially those with lower inhibitory control, are particularly vulnerable (Anzman and Birch 2009;Rollins et al 2014).…”
Section: Parenting Practices: Restricting Children's Consumption Of Umentioning
confidence: 99%
“…Restricting children's access to a preferred food is a feeding practice often applied by parents (Rollins, Loken, Savage, & Birch, 2014a). Studies have indicated that restriction tends to increase preferences for the restricted food and might lead to overeating behaviour when that food is made available.…”
Section: Family Communication Patterns Theorymentioning
confidence: 99%